Enacting the Work of Language Instruction: High-Leverage Teaching Practices - Glisan, Eileen W; Donato, Richard (American Council on the Teaching of Foreign Languages, 2017)
This book presents an approach to teacher education and professional development that emphasizes carefully deconstructing fundamental instructional practices that are complex and often not visible through observation, definition, or brief explanation. Its goal is to assist teachers in learning how to enact specific practices, referred to as high-leverage teaching practices, deemed essential to foreign language teaching and situated in theory and research. Six practices are presented: (1) Facilitating Target Language Comprehensibility; (2) Building a Classroom Discourse Community; (3) Guiding Learners to Interpret and Discuss Authentic Texts; (4) Focusing on Form in a Dialogic Context Through PACE; (5) Focusing on Cultural Products, Practices, and Perspectives in a Dialogic Context; and (6) Providing Oral Corrective Feedback to Improve Learner Performance. Unique features of the book include deconstruction of each practice, activities for rehearsing the practices, rubrics for assessing performance, tools to assist teachers in enacting the practices, and discussion of how each practice relates to larger educational issues.